NHC-Ag/Pd-Catalyzed Reductive Carboxylation of Terminal Alkynes with CO2 and H2: A Combined Experimental and Computational Study for Fine-Tuned Selectivity - Yu, Dingyi (2017)
Reductive carboxylation of terminal alkynes utilizing CO2 and H2 as reactants is an interesting and challenging transformation. Theoretical calculations indicated it would be kinetically possible to obtain cinnamic acid, the reductive carboxylation product, from phenylacetylene in a CO2/H2 system with an N-heterocyclic carbene (NHC)-supported Ag/Pd bimetallic catalysts through competitive carboxylation/hydrogenation cascade reactions in one step. These calculations were verified experimentally with a poly-NHC-supported Ag/Pd catalyst. By tuning the catalyst composition and reaction temperature, phenylacetylene was selectively converted to cinnamic acid, hydrocinnamic acid, or phenylpropiolic acid in excellent yields.